OCCURRENCE OF SMALL HOMOLOGOUS AND COMPLEMENTARY FRAGMENTS IN HUMAN VIRUS GENOMES AND THEIR POSSIBLE ROLE - E. P. Kharchenko (Инфекция и иммунитет, 2018)
With computer analysis occurrence of small homologous and complementary fragments (21 nucleotides in length) has been studied in genomes of 14 human viruses causing most dangerous infections. The sample includes viruses with (+) and (–) single stranded RNA and DNA-containing hepatitis A virus. Analysis of occurrence of homologous sequences has shown the existence two extreme situations. On the one hand, the same virus contains homologous sequences to almost all other viruses (for example, Ebola virus, severe acute respiratory syndrome-related coronavirus, and mumps virus), and numerous homologous sequences to the same other virus (especially in severe acute respiratory syndrome-related coronavirus to Dengue virus and in Ebola virus to poliovirus). On the other hand, there are rare occurrence and not numerous homologous sequences in genomes of other viruses (rubella virus, hepatitis A virus, and hepatitis B virus). Similar situation exists for occurrence of complementary sequences. Rubella virus, the genome of which has the high content of guanine and cytosine, has no complementary sequences to almost all other viruses. Most viruses have moderate level of occurrence for homologous and complementary sequences. Autocomplementary sequences are numerous in most viruses and one may suggest that the genome of single stranded RNA viruses has branched secondary structure. In addition to possible role in recombination among strains autocomplementary sequences could be regulators of translation rate of virus proteins and determine its optimal proportion in virion assembly with genome and mRNA folding. Occurrence of small homologous and complementary sequences in RNA- and DNA-containing viruses may be the result of multiple recombinations in the past and the present and determine their adaptation and variability. Recombination may take place in coinfection of human and/or common hosts. Inclusion of homologous and complementary sequences into genome could not only renew viruses but also serve as memory of existence of a competitor for host and means of counteraction against a competitor in coinfection being an analogy of the bacterial CRISPR/Cas system.